ANTIBIOTIC RESISTANCE PATTERN AGAINST VARIOUS ISOLATES OF STAPHYLOCOCCUS AUREUS FROM RAW MILK SAMPLES - Farzana, Kalsoom; Shah, Syed Nisar Hussain; Jabeen, Farzana (Journal of Research (Science), 2025)
A total of 50 raw milk samples were taken from shops in Multan city. More than 40% milk samples were found contaminated more than 108 bacteria per ml. The coagulase-positive Staphylococcus aureus was present in all the samples. When the coagulase-positive Staphylococcus aureus isolates were subjected to antibiotic sensitivity test, the erythromycin was the most effective antibiotic. Only 10% isolates were found methicillin resistant, co-trimaxazole, showed maximum resistance rate 81.81%, 57% isolates were resistant to lincomycin, 63.63% to orbenin, 25.97% to ampicillin, 24.67% to penicillin 23.37% to augmentin and 18.18% to ampiclox. Only 2.6% of the isolates were found resistant to tetracycline. It is concluded that hygiene of milk is poor and resistant strains have contaminated the milk probably during the process of transportation.